(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The special external environment is a constantly changing and evolving environment. Although it is important as a key measure of the success or failure of an organization, it is difficult to be managed or controlled completely, due to the changes and transformations that affect on it constantly, and the opportunities that can be used to strengthen the competitivity, as well as threats imposed by that environment and their impact on the organization’s work in a negatively. Therefore, these threats must be identified and avoided or minimize their impact and turned them into opportunities that can be utilized. This research aims to study the impact of the special external environment in competitive decision making. To achieve this goal, a questionnaire was distributed to the staff of the Commercial Bank of Syria in the four branches of Latakia. The study concluded that there are significant differences between the special external environment’s analysis and the competitive decision making at a significant level <0.05 using SPSS Application. تعد البيئة الخارجية الخاصة بيئة متغيرة ومتبدلة بشكل مستمر. وعلى الرغم من أهميتها بوصفها مقياساً رئيساً لنجاح أية منظمة أو فشلها، إلا أنه يصعب التحكم فيها أو السيطرة عليها بشكل كامل. وذلك تبعاً للتغيرات والتبدلات التي تطرأ عليها باستمرار، وما يمنحه ذلك من فرص يمكن الإفادة منها لتدعيم المركز التنافسي. فضلاً عن التهديدات التي تفرضها تلك البيئة، وتأثير ذلك كله على عمل المنظمة بشكل سلبي. وبالتالي لا بدّ من التعرف على هذه التهديدات والعمل على تجنبها أو التقليل من أثرها وتحويلها إلى فرص يمكن الإفادة منها. من هنا، فإن هدف البحث هو دراسة تأثير البيئة الخارجية الخاصة في اتخاذ القرار التنافسي. ولتحقيق ذلك تم توزيع استبانة على موظفي المصرف التجاري السوري في الفروع الأربعة في اللاذقية. وخلصت الدراسة إلى وجود فروق جوهرية بين تحليل البيئة الخارجية الخاصة واتخاذ القرار التنافسي عند مستوى معنوية <0.05 باستخدام برنامج spss.